Early results of coronary artery bypass grafting with coronary endarterectomy for severe coronary artery disease - Schmitto, Jan D (BioMed Central, 2009)
BACKGROUND: Despite the existence of controversial debates on the efficiency of coronary endarterectomy (CE), it is still used as an adjunct to coronary artery bypass grafting (CABG). This is particularly true in patients with endstage coronary artery disease. Given the improvements in cardiac surgery and postoperative care, as well as the rising number of elderly patient with numerous co-morbidities, re-evaluating the pros and cons of this technique is needed. METHODS: Patient demographic information, operative details and outcome data of 104 patients with diffuse calcified coronary artery disease were retrospectively analyzed with respect to functional capacity (NYHA), angina pectoris (CCS) and mortality. Actuarial survival was reported using a Kaplan-Meyer analysis. RESULTS: Between August 2001 and March 2005, 104 patients underwent coronary artery bypass grafting (CABG) with adjunctive coronary endarterectomy (CE) in the Department of Thoracic-, Cardiac- and Vascular Surgery, University of Goettingen. Four patients were lost during follow-up. Data were gained from 88 male and 12 female patients; mean age was 65.5 ± 9 years. A total of 396 vessels were bypassed (4 ± 0.9 vessels per patient). In 98% left internal thoracic artery (LITA) was used as arterial bypass graft and a total of 114 vessels were endarterectomized. CE was performed on right coronary artery (RCA) (n = 55), on left anterior descending artery (LAD) (n = 52) and circumflex artery (RCX) (n = 7). Ninety-five patients suffered from 3-vessel-disease, 3 from 2-vessel- and 2 from 1-vessel-disease. Closed technique was used in 18%, open technique in 79% and in 3% a combination of both. The most frequent endarterectomized localization was right coronary artery (RCA = 55%). Despite the severity of endstage atherosclerosis, hospital mortality was only 5% (n = 5). During follow-up (24.5 ± 13.4 months), which is 96% complete (4 patients were lost caused by unknown address) 8 patients died (cardiac failure: 3; stroke: 1; cancer: 1; unknown reasons: 3). NYHA-classification significantly improved after CABG with CE from 2.2 ± 0.9 preoperative to 1.7 ± 0.9 postoperative. CCS also changed from 2.4 ± 1.0 to 1.5 ± 0.8 CONCLUSION: Early results of coronary endarterectomy are acceptable with respect to mortality, NYHA & CCS. This technique offers a valuable surgical option for patients with endstage coronary artery disease in whom complete revascularization otherwise can not be obtained. Careful patient selection will be necessary to assure the long-term benefit of this procedure.